2014
DOI: 10.1074/jbc.m113.528638
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role for Piezo1 in Stretch-evoked Ca2+ Influx and ATP Release in Urothelial Cell Cultures

Abstract: Background: The Piezo1 channel was recently identified as a genuine mechanosensor in mammalian cells. Results: Urothelial cells exhibited a Piezo1-dependent increase in cytosolic Ca 2ϩ concentrations in response to mechanical stretch stimuli, leading to ATP release. Conclusion: Piezo1 senses extension of the bladder urothelium, which is converted into an ATP signal. Significance: Inhibition of Piezo1 might provide a new treatment for bladder dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
285
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(301 citation statements)
references
References 61 publications
14
285
2
Order By: Relevance
“…Piezo1 has been implicated in cellular processes in which cells respond to an external mechanical force, e.g., a stretch stimulus, osmotic pressure, or shear stress (31,33,34,(36)(37)(38). We asked whether cell-generated forces, such as traction forces, also can activate Piezo1.…”
Section: Resultsmentioning
confidence: 99%
“…Piezo1 has been implicated in cellular processes in which cells respond to an external mechanical force, e.g., a stretch stimulus, osmotic pressure, or shear stress (31,33,34,(36)(37)(38). We asked whether cell-generated forces, such as traction forces, also can activate Piezo1.…”
Section: Resultsmentioning
confidence: 99%
“…Volume 126 Number 12 December 2016 studies using urothelial cells and red blood cells have also shown a PIEZO1-mediated mechanotransductive release of ATP, indicating that this is a cellular mechanism not restricted to endothelial cells (48,49). However, the process of PIEZO1-mediated ATP release from endothelial cells appears to involve additional mechanisms that still need to be fully explored.…”
Section: +mentioning
confidence: 99%
“…Primary Culture of Mouse Urothelial Cells-Following anesthesia, whole bladders were separated, and urothelial cells were prepared by the methods described previously with slight mod-ifications (17,18). The everted bladder was incubated with papain (6 l/ml) for 25 min at 37°C with just one tapping for 15 min after incubation.…”
Section: Methodsmentioning
confidence: 99%